Electrooptical Synergy on Plasmon–Exciton‐Codriven Surface Reduction Reactions. Issue 24 (9th November 2017) - Cao, En; Guo, Xiao; Zhang, Liqiang; Shi, Ying; Lin, Weihua; Liu, Xiaochun; Fang, Yurui; Zhou, Liyan; Sun, Yinghui; Song, Yuzhi; Liang, Wenjie; Sun, Mengtao
Abstract: The monolayer graphene–Ag nanoparticles hybrid system is fabricated as the electrooptical‐coordinated controlled substrate for surface‐enhanced Raman scattering spectroscopy. Plasmon–exciton interactions in this hybrid system are systemically investigated and applied in the field of surface catalytic reactions, manipulated by the electrooptical synergy. Experimental results demonstrate that the surface catalytic reactions can not only be controlled by plasmon–exciton coupling, but also be affected by the gate voltages and electric currents (or bias voltages). The gate voltage can tune the density of state of electrons, and electric current can make the hot electrons near the Fermi level with higher kinetic energy. Both of gate voltages and electric currents can significantly promote the efficiency and probability of plasmon–exciton‐codriven surface catalytic reactions. The electrooptical device based on plasmon–exciton coupling can be potentially applied in the fields of sensor, catalysis, energy, and environment. Abstract : An electrical‐manipulated plasmon–exciton coupling device, based on monolayer graphene–Ag nanoparticles hybrid system, is fabricated as the surface‐enhanced Raman scattering substrate. The gate voltage can increase density of state of hot electrons on the conduction band of graphene, and bias voltage can make hot electrons with higher kinetic energy. Both gate voltage and electrical currents can significantly promote plasmon–exciton‐codriven surface catalytic reaction.